Saliva profiles in children with congenital heart disease - Figen Seymen; Yegane Guven; Ezel Uslu; Merve Bayram; Sule Batu; Mine Koruyucu (Istanbul University, 2020)
Purpose The low salivary pH and buffering capacity are caused by using heart failure medications. For this reason oral health should be supported in cardiac patients, it is necessary that they attend dental clinics for regular follow up. The aim of this study is to evaluate the relationship between the salivary oxidative stress markers and salivary pH, salivary buffering capacity, salivary flow rate and dental caries of children with congenital heart disease (CHD). Material and Methods This cross sectional study was carried out with 42 CHD and 42 healthy children. The participants' gender, age, general health and medications, and caries scores (dfs/ DMFS) were written down, then their unstimulated saliva samples were collected. These specimens were evaluated in terms of the salivary secretion rate, salivary buffering capacity, pH, protein levels, superoxide dismutase (SOD), ferric reducing antioxidant power (FRAP), the thiobarbituric acid reactive substances (TBARS), protein carbonyl, protein thiols, total sialic acid. Results Both groups showed caries at similar levels. The salivary pH and buffering capacity were significantly less in the children with CHD than in the controls. The levels of TBARS and protein carbonyl were significantly higher in the children with CHD than in the controls. There was not any significant difference relating to the mean salivary secretion rate, protein levels, SOD, FRAP, protein thiols and total sialic acid. Conclusion The elevated TBARS and protein carbonyl levels in the patients with CHD were observed as an indicator of the free radical damage leading to oxidative stress.